Effect of infusion tests on the dynamical properties of intracranial pressure in hydrocephalus. Issue 134 (October 2016) - García, María; Poza, Jesús; Bachiller, Alejandro; Santamarta, David; Hornero, Roberto
Highlights: Wavelet turbulence and entropy revealed changes in the ICP signals during ITs. Changes in similarity, irregularity and variability of ICP signals were found. Significant differences in B2 can be related to ICP pulse waves. Only slight differences were found in B1, associated with ICP respiratory waves. Abstract: Background and objective: Hydrocephalus comprises a number of conditions characterised by clinical symptoms, dilated ventricles and anomalous cerebrospinal fluid (CSF) dynamics. Infusion tests (ITs) are usually performed to study CSF circulation and in the preoperatory evaluation of patients with hydrocephalus. The study of intracranial pressure (ICP) signals recorded during ITs could be useful to gain insight into the underlying pathophysiology of this condition and to further support treatment decisions. In this study, two wavelet parameters, wavelet turbulence ( WT ) and wavelet entropy ( WE ), were analysed in order to characterise the variability, irregularity and similarity in spectral content of ICP signals in hydrocephalus. Methods: One hundred and twelve ICP signals were analysed using WT and WE . These parameters were calculated in two frequency bands: B1 (0.15–0.3 Hz) and B2 (0.67–2.5 Hz). Each signal was divided into four artefact-free epochs corresponding to the basal, early infusion, plateau and recovery phases of the IT. We calculated the mean and standard deviation of WT and WE and analysed whether these parameters revealed differences between epochs of the IT. Results: Statistically significant differences ( p < 1.70⋅10 −3, Bonferroni-corrected Wilcoxon signed-rank tests) in pairwise comparisons between phases of ITs were found using the mean and standard deviation of WT and WE . These differences were mainly found in B2 . Conclusions: Wavelet parameters like WT and WE revealed changes in the signal time-scale representation during ITs. Statistically significant differences were mainly found in B2, associated with ICP pulse waves, and included a higher degree of similarity in the spectral content, together with a lower irregularity and variability in the plateau phase with respect to the basal phase.